Power Consumption and Power Saving Potential at Enterprises of Consumer Industry - V. N. Romaniuk; D. b Muslina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper considers a potential of power saving at enterprises of consumer industry in theRepublicofBelaruswhile making transition to co-generation power supply of heat technological processes.